Human Cystic Echinococcosis: Old Problems and New Perspectives - Siracusano, Alessandra; Teggi, Antonella; Ortona, Elena (Interdisciplinary Perspectives on Infectious Diseases, 2009)
Cystic echinococcosis (CE) is a widespread chronic endemic helminthic disease caused by infection with metacestodes of the tapeworm Echinococcus granulosus. CE affects humans and has a worldwide prevalence of approximately six million. In this review, we discuss current findings in diagnosis and clinical management of CE and new concepts relating to E. granulosus molecules that directly modulate the host immune responses favouring a strong anti-inflammatory response and perpetuating parasite survival in the host. New insights into the molecular biology of E. granulosus will improve considerably our knowledge of the disease and will provide new potential therapeutic applications to treat or prevent inflammatory immune-mediated disease.